Study of heat sink effect of blood in a bifurcated vessel. Issue 6 (26th April 2023) - Das, Sidharth Sankar; Mahapatra, Swarup Kumar
Abstract: Thermal ablation treatment uses elevated (hyperthermia) or depressed (hypothermia) tissue temperature to destroy tumor cells. The efficacy and effectiveness of thermal ablation therapy is dependent on the tissue temperature which is significantly affected due to heat sink effect of blood flow near the infected site. In this study, Euler-Euler multiphase model is used to analyze the effect of plasma and RBC concentration on the heat sink effect of blood in a bifurcated vessel. This study is divided into two separate cases. First case refers to the study of heat sink effect produced by a tumor patient suffering from HVS (hyperviscosity syndrome) and a normal (without blood disorder) tumor patient during hyperthermia treatment. The second case analyses the effect of RBCs on blood heat transfer. Temperature distribution and transient Nusselt number, which are used to represent heat sink effect, are calculated and compared for different cases of blood disorders. From the results, it is found that a patient with HVS blood disorder produces a smaller heat sink effect during hyperthermia treatment compared to a normal tumor patient. Also, the level of RBC concentration in the blood stream has a minimal effect on heat transfer.